FETISISME KOMODITAS SMARTPHONE APPLE (iPhone) DI KALANGAN MAHASISWA/I FISIP UNIVERSITAS UDAYANA - Nurbaity, Fava; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT This study discusses the fetishism (worship one brand in obsessional manners) of smart phone Apple brand (iPhone) among Udayana University students, along with the meaning and its utilization. The research approach is qualitative method by conducting in-depth interviews with twenty informants from Faculty of Social and Political Sciences in the area of Sudirman street campus of Udayana University, and analyzing the result using Commodity Fetishism theory by Martyn J. Lee. Fanatics users of Apple brand (iPhone) explained their worship on it is based on various reasons and backgrounds, such as qualities and usefulness, qualified self-confidence, to the deliberate participation of lifestyles that are of public concern today. Value use, symbol value, and exchange value are the main reasons in brand selection to add and confirm status and identity of the person. Based on this, unavoidably that advertising has an important role in making an object producing value and meaning. Keywords: Apple (iPhone) Smartphone, Commodity Fetishism, Student